COVID-19 mental health care toolkit: an international collaborative effort by Early Career Psychiatrists section - Adiukwu, Frances (Gen Psychiatr, 2020)
The collaborative effort of an international research team from the Early Career Psychiatrists section of the World Psychiatry Association has brought about an easy-to-use, quick and stepwise mental health care toolkit for the identification and appropriate referral of those in need of mental health care during the pandemic. This simple guide can be applied in the general outpatient setting and is catered for all healthcare professionals, regardless of their expertise within the mental health field with minimal training. It is our hope that by incorporating this toolkit into our daily clinical care during the pandemic for high-risk patients and patients with non-specific complaints, we will be able to bridge the mental health gap present in our society.